Modelagem fenomenológica da síntese enzimática de biodiesel etanólico utilizando lipase solúvel - Villegas Aguilar, María Carlota (2018)
The kinetics study of the synthesis of ethyl biodiesel allows a deeper understanding of the enzymatic process, providing an important tool for process design, optimization and control. Most of the models proposed in the literature for enzymatic biodiesel production use methanol and immobilized lipases. Moreover, depending on the source of the lipase and the reaction medium, the reaction may have a distinct mechanism. In this work we study the biodiesel production by transesterification of refined soybean oil and bioethanol using the soluble lipase NS-40116, a liquid formulation of a genetic modified lipase from Thermomyces lanuginosus. The aim of this research is to develop a phenomenological model capable of describing the catalytic behavior of that lipase formulation in this heterogeneous medium. Batch assays were carried out in a bench jacketed glass reactor where several process variables were varied: agitation speed (800-1200 rpm), enzyme concentration (0.5-2.0%w/woil) and alcohol content (1.5-2.0 equivalent). All assays were carried out at 35°C with 10%w/woil of water. In addition, the relationship between the agitation speed and the volumetric flow rate of the substrates with the oil-water-alcohol emulsion interface was determined. The soluble lipase NS-40116 was characterized: protein content 31.454 ± 0.002 mg protein/ml lipase, hydrolytic activity 48048 ± 653 LU/ml (1 LU: activity required to produce 1 μmol/min with standard conditions) and molecular weight 31 kDa. An ethyl biodiesel was obtained from refined soybean oil with a concentration of esters: 82.55 ± 7.17% (T = 35°C, 800 RPM, 10%w/woil water, 2.0%w/woil lipase and 2.0 eq. ethyl alcohol). The average interfacial area was evaluated by measuring droplet diameters distribution in pictures of the emulsion obtained in a microscope. Different agitation speeds and polar/nonpolar volume ratios were used. Results show that the average diameter of the droplets increases when the polar volume increases and decreases with the agitation speed. The kinetic parameters were determined for the mathematical model of the enzymatic synthesis of ethyl biodiesel using the soluble lipase NS-40116.